The Effect Of Elderly Gymnastics On Blood Pressure In Hypertensive Elderly - Salsabila, Noor; Sajidah, Ainun; Mariana, Evi Risa; Nurhayati, Nurhayati; Suroto, Suroto (JURNAL CITRA KEPERAWATAN, 2024)
Hypertension in the elderly generally comes from changes in the condition of arterial blood vessels that become harder and less elastic. To prevent hypertension, one of them is doing elderly gymnastics. The purpose of this study was to analyse the effect of elderly gymnastics on blood pressure in hypertensive elderly at Panti Perlindungan dan Rehabilitasi Sosial Lanjut Usia (PPRSLU) Budi Sejahtera Martapura. The research method uses Pre-Experimental research type with one group pretest and posttest design. Sampling using purposive sampling with a sample size of 11 respondents. Analysis using paired sample t-test statistical test with ɑ 0.05. The results showed that there was an effect of elderly gymnastics on systolic blood pressure with a p value of 0,029 (<0.05) and no effect of elderly gymnastics on diastolic blood pressure with a p value of 0,185 (>0.05). It can be concluded that there is an effect of elderly gymnastics on blood pressure in hypertensive elderly. It is hoped that hypertensive elderly people will always routinely participate in elderly gymnastics and maintain health patterns to avoid hypertension.